Peranan Alumni Ilmu Komunikasi Penyiaran Islam dalam Pengembangan Dakwah Islamiyah di Kota Padangsidimpuan: Studi Kasus Fakultas Dakwah dan Ilmu Komunikasi IAIN Padangsidimpuan - Amran, Ali; Agustin, Oriza; Ritonga, Anas Habibi; Wijaya, Muhammad Rudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
The low alumni of the Department of Islamic Broadcasting Communication (KPI) who have roles in accordance with their educational competence as preachers and religious instructors have the effect of lack of contribution in the development of Islamic da'wah, one of which is in Padangsidimpuan City. This affects the interest of the community and the future development of the KPI Department. This research was conducted to determine the driving and inhibiting factors of the role of KPI Department alumni in developing Islamic da'wah in Padangsidimpuan. This qualitative research uses a descriptive exploratory method in the form of field studies in the City of Padangsidimpuan. The results revealed that there was a role for alumni in the development of Islamic da'wah in Padangsidimpuan City as a preacher / religious preacher and religious instructor according to his competence. This role is driven by the mastery of propaganda material and good character, and the ability to socialize with the community. However, there are still weaknesses in mastering fiqh material and the lack of relationships in society.